(untitled) (Research, Society and Development, 2021)
Motivated by technological and environmental needs, membrane separation processes have shown a great improvement over traditional techniques. These benefits encourage the application of membrane separations and stimulate development in purification and sterilization processes in the pharmaceutical and food industries in general. In addition, they are used in the water treatment for industrial or urban use, desalination, gas separation, clarification of juices, hemodialysis and in the effluents treatment. The latter is the application that this work is intended for, especially in the separation of water from textile dyes, i.e., indigo blue. Thus, polysulfone membranes were synthesized in the form of hollow fiber, with varying levels of alumina, for use in the effluents treatment. The morphological characteristics, hydrophilicity, flow measurements and the turbidity measurement of the prepared membranes were evaluated. The membranes were produced by the phase inversion method, via cold extrusion, immersion - precipitation. Filtration experiments indicate that alumina particles can increase the flow of water by improving the hydrophilicity of the membrane. By SEM images, a larger amount of pores, of smaller sizes, was verified with the insertion of alumina in the polysulfone. Thus, through the analysis of the Turbidimeter, the amount of indigo blue particles suspended in the membrane with alumina was smaller, since the pores are smaller and their greater quantity, generating a greater removal of the dye. Thus, with the increase in the alumina content, the separation between water and the indigo blue dye was improved.